Evaluating the performance of climate models in reproducing the hydrological characteristics of rainfall events. Issue 9 (3rd July 2020) - Song, Jung-Hun; Her, Younggu; Shin, Satbyeol; Cho, Jaepil; Paudel, Rajendra; Khare, Yogesh P.; Obeysekera, Jayantha; Martinez, Christopher J.
ABSTRACT: Rainfall events largely control hydrological processes occurring on and in the ground, but the performance of climate models in reproducing rainfall events has not been investigated enough to guide selection among the models when making hydrological projections. We proposed to compare the durations, intensities, and pause periods, as well as depths of rainfall events when assessing the accuracy of general circulation models (GCMs) in reproducing the hydrological characteristics of observed rainfall. We also compared the sizes of design storm events and the frequency and severity of drought to demonstrate the consequences of GCM selection. The results show that rainfall and extreme hydrological event projections could significantly vary depending on climate model selection and weather stations, suggesting the need for a careful and comprehensive evaluation of GCM in the hydrological analysis of climate change. The proposed methods are expected to help to improve the accuracy of future hydrological projections for water resources planning.